2017
DOI: 10.1002/jcph.911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Alfentanil on Nonpainful Thermally Induced Hyperalgesia in Healthy Volunteers

Abstract: Experimental interventions that activate specific components of clinical pain are necessary for characterization of underlying mechanisms and pharmacology. Cutaneous hyperalgesia has been described that uses non-painful heat to induce secondary hyperalgesia. This study evaluated the effect intravenous alfentanil on experimental cutaneous hyperalgesia created using this method. Eighteen subjects participated in a randomized, double-blinded, placebo controlled crossover study consisting of two sessions, one with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Initial techniques using small skin spots at >50°C on glabrous skin were instrumental in clarifying many aspects of peripheral encoding of heat pain (Meyer & Campbell, 1981 ; Raja et al., 1984 ) (Table 3 ), but produced second degree burns, blisters and visible oedema, and have been replaced by techniques using lower temperatures on hairy skin. Prolonged thermal stimulation at non‐painful levels (40–42°C) can also trigger secondary hyperalgesia; however, the stimulus has to be maintained for long periods, and hyperalgesia is extremely short‐lived (Cervero et al., 1993 ; Schifftner et al., 2017 ). Therefore, most studies used thermodes at higher temperatures (~47°C) applied during 5–7 min to a 9–16 cm 2 hairy skin contact area (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial techniques using small skin spots at >50°C on glabrous skin were instrumental in clarifying many aspects of peripheral encoding of heat pain (Meyer & Campbell, 1981 ; Raja et al., 1984 ) (Table 3 ), but produced second degree burns, blisters and visible oedema, and have been replaced by techniques using lower temperatures on hairy skin. Prolonged thermal stimulation at non‐painful levels (40–42°C) can also trigger secondary hyperalgesia; however, the stimulus has to be maintained for long periods, and hyperalgesia is extremely short‐lived (Cervero et al., 1993 ; Schifftner et al., 2017 ). Therefore, most studies used thermodes at higher temperatures (~47°C) applied during 5–7 min to a 9–16 cm 2 hairy skin contact area (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thermode‐induced 2HA was decreased by systemic opioids including morphine, buprenorphine and alfentanil in seven studies (six controlled; Table 6 ), but failed to overpower placebo in four controlled trials (Lillesø et al., 2000 ; Ravn et al., 2014 ; Schifftner et al., 2017 ; Warncke et al., 1997 ). Gabapentin decreased 2HA in two controlled studies (Dirks et al., 2002 ; Petersen et al., 2014 ) and showed a trend in a third one ( p =.06; Werner et al., 2001 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of respiratory depression was low in both groups. Alfentanil inhibits breathing to a lesser extent than other opioids and has a lower incidence of choking [ 38 ]. Pre-oxygenation and slow bolus administration can reduce respiratory depression.…”
Section: Discussionmentioning
confidence: 99%
“…There continues to be debate regarding this somewhat elusive condition and its legitimacy as clinical entity requiring attention and treatment. Most studies conducted in humans revolve around rapid-acting intravenous opioids such as alfentanil (7) and remifentanil (8), in acute hyperalgesic states created experimentally (1), or else in recovering drug addicts, and have not been as precise in defining the role of OIH with chronic oral consumption of opioids. Electrophysiological studies have shown that remifentanil elicits rapid and prolonged upregulation of N-methyl-D-aspartate receptor (NMDAR) currents, which may contribute to the development of OIH.…”
Section: Opioid-induced Hyperalgesia: Myth or Burgeoning Public Health Crisis?mentioning
confidence: 99%